Refugee Status in Japan: Change of Judicial Practice in the Democratic State - Arakaki, Osamu (Victoria University of Wellington Law Review, 2007)
This article considers the practice of Japanese courts in determining appeals to administrative determinations of refugee status in the 1980s and 1990s. Contrasting Japanese practice with that of New Zealand, the author highlights how the approach taken by the Japanese courts was characterised by conservatism and unwillingness to consider international jurisprudence. The author discusses how Japanese judges have appeared unfamiliar with internationally accepted concepts of refugee law, and also reveals that in the practice of the 1980s and 1990s attorneys were insufficiently knowledgeable about refugee law. The author concludes by discussing ways in which Japanese practice has evolved since 2000, and considers some possible reasons for this development.